2023
DOI: 10.3390/buildings13020311
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Social Cultural and Economic Benefits of Green Buildings Based on Improved AHP–FCE Method

Abstract: Green buildings can effectively alleviate energy scarcity and improve environmental quality, and are becoming the mainstream mode of transformation and upgrading of the construction industry. It is given great importance by all sectors of society committed to implementing the “carbon peak” and “carbon neutral” goals earnestly. However, the unclear comprehensive benefits of green buildings restrict their development in China. The existing studies tend to be limited to a single aspect, such as economic benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Context-specific policies for rebound mitigation should be implemented to address rebound effects [61,62]. Furthermore, it is essential to consider the multidimensional and long-lasting impact of energy efficiency measures and their direct and indirect benefits (e.g., [56,63,64]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Context-specific policies for rebound mitigation should be implemented to address rebound effects [61,62]. Furthermore, it is essential to consider the multidimensional and long-lasting impact of energy efficiency measures and their direct and indirect benefits (e.g., [56,63,64]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, the term "green building" identifies buildings with a reduced environmental impact; however, it is often used synonymously with "sustainable building," which connotes a building that is capable of being sustained as it permanently limits resource depletion or damage [34]. Moreover, it is reported that sustainable or green buildings are capable of generating various benefits on all three dimensions of sustainability-environmental, economic, and social [35][36][37][38][39]. Indeed, the intent of sustainable and/or high-performance building is to [34,35,37,39] mitigate impacts on the environment by decreasing consumption, improving efficiency, and promoting biodiversity and the use of renewable resources; protect and improve the health, safety, and welfare conditions of building users; and optimize direct and indirect economic costs and returns.…”
Section: Theoretical Evaluation Frameworkmentioning
confidence: 99%
“…Moreover, it is reported that sustainable or green buildings are capable of generating various benefits on all three dimensions of sustainability-environmental, economic, and social [35][36][37][38][39]. Indeed, the intent of sustainable and/or high-performance building is to [34,35,37,39] mitigate impacts on the environment by decreasing consumption, improving efficiency, and promoting biodiversity and the use of renewable resources; protect and improve the health, safety, and welfare conditions of building users; and optimize direct and indirect economic costs and returns. More specifically, starting from the revised references, Table 1 shows the theoretical evaluation framework composed of the main 9 key themes and the related 31 benefits triggered by sustainable/green buildings with respect to the three dimensions of sustainability-environmental, social and economic.…”
Section: Theoretical Evaluation Frameworkmentioning
confidence: 99%
“…China has entered a new stage of implementing the "carbon peaking and carbon neutrality goals". At present, all industries have begun the low-carbon transformation, the existing literature mainly focus on low carbon development concepts, carbon emission assessment, digital technology applications, low carbon production benefits [1][2][3][4], etc. Logistics is a strategic and fundamental industry that supports the national economic activities, which should pay more attention to the green development process.…”
Section: Introductionmentioning
confidence: 99%
“…Fig6Bshows the LCER between two scenarios. Under the lowcarbon scenario, the LCER in Nanjing increased by an average of4 tons compared with the baseline scenario. The average annual growth rate of the carbon emission reduction increased from 6.18% to 11.12%, and the growth trend was steeper.…”
mentioning
confidence: 96%